Avaliação dos efeitos da cetamina racêmica, cetamina s (+) e midazolam em jibóias boa constrictor linnaeus, 1758 (squamata: boidae) - Simone, Simone Borges Salgueiro de (2011)
CHAPTER 2: Since growth in the creation of exotic snakes as pets, beyond its use in a commercial scale, pharmacological restraint used during medical and surgical procedures has become essential. Thus, the objective was to compare the effects of racemic ketamine and S(+)-ketamine in Boa constrictor. We used 20 redtail boas, divided into two groups of ten animals. Group 1 (G1) received racemic ketamine and group 2 (G2) S(+)-ketamine, both at a dose of 20 mg/kg IC. Physiological parameters showed that the snakes had lethargic behavior with decreased muscle tone, head tone, movement and loss of aggressiveness. The specimens of G1 remained in the score 2 for the head tone, muscle tone, manipulation and locomotion by 128 ± 47.85 minutes and the representatives of G2 by 171.50 ± 55.43 minutes. Only 50% of the animals of group 2 reached the reasonable period of anesthesia, because they have lost postural righting reaction by 50.60 ± 33.75 minutes and analgesia achieved by only 67.5 ± 10.61 minutes. The turnaround time t0 conditions were 174 ± 46.48 minutes for the G1 and 258 ± 61.97 minutes for G2. There were no significant differences between the assessment of heart rate and respiratory rate in both groups. It was concluded therefore that there is a superiority of S(+)-ketamine over the racemic form. However, the recovery period the S(+)-isomer was greater than that observed with racemic ketamine in Boa constrictor. The protocols are evaluated for the listed drug containment of the species studied, little or procedures for non-invasive. CHAPTER 3: Given the increase in the breeding of snakes in captivity and focus on the preservation of wild specimens, knowledge about the anesthesia of these animals has become essential, given the increased demand for medical and surgical care. Thus, the objective was to compare the effects of midazolam in Boa constrictor. We used 20 redtail boas, divided into two groups of ten animals. Group 1 (G1) received midazolam 1 mg/kg and group 2 (G2) 2 mg/kg, via IC. In the G1 the specimens remained in score 2 for the head tone, muscle tone, manipulation and locomotion for 233.50 ± 71.34 minutes and the representatives of G2 for 328.50 ± 125.35 minutes. No redtail boa belonging to both the G1 and G2 lost the RPE or achieved analgesia. However, there was an intense muscle relaxation and a difficult to move in all specimens tested. The turnaround time t0 conditions were 279 ± 73.55 minutes for the G1 and 372 ± 142.27 minutes for the G2. There were no statistical differences between evaluations of heart and respiratory rates in both groups tested. It was found that the snakes had lethargic behavior with decreased muscle tone, head tone, movement and loss of aggressiveness. It was concluded therefore, in redtail boa midazolam at dosage of 1 mg/kg causes the same effect as midazolam 2 mg/kg, but with less recovery time and can be used to contain Boa constrictor, or associations aimed at an effective muscle relaxation.